Coexistence of nonfluorescent chromoproteins and fluorescent proteins in massive Porites spp. corals manifesting a pink pigmentation response - Suzuki, Toshiyuki; Casareto, Beatriz E.; Yucharoen, Mathinee; Dohra, Hideo; Suzuki, Yoshimi (Frontiers in Physiology, 2024)
Introduction: Several fluorescent proteins (FPs) and chromoproteins (CPs) are present in anthozoans and play possible roles in photoprotection. Coral tissues in massive corals often display discoloration accompanied by inflammation. Incidences of the pink pigmentation response (PPR) in massive Porites, described as inflammatory pink lesions of different shapes and sizes, has recently increased worldwide. FPs are reported to be present in PPR lesions, wherein a red fluorescent protein (RFP) appears to play a role in reducing reactive oxygen species. However, to date, the biochemical characterization and possible roles of the pigments involved are poorly understood. The present study aimed to identify and characterize the proteins responsible for pink discoloration in massive Porites colonies displaying PPRs, as well as to assess the differential distribution of pigments and the antioxidant properties of pigmented areas.Method: CPs were extracted from PPR lesions using gel-filtration chromatography and identified via genetic analysis using liquid chromatography-tandem mass spectrometry. The coexistence of CPs and RFP in coral tissues was assessed using microscopic observation.Photosynthetic antivity and hydrogen peroxide-scavenging activitiy were measured to assess coral stress conditions.Results: The present study revealed that the same CP (plut2.m8.16902.m1) isolated from massive Porites was present in both the pink spot and patch morphologies of the PPR. CPs were also found to coexist with RFP in coral tissues that manifested a PPR, with a differential distribution (coenosarc or tip of polyps' tentacles). High hydrogen peroxide-scavenging rates was found in tissues affected by PPR.Discussion and Conclusions: The coexistence of CPs and RFP suggests their possible differential role in coral immunity. CPs, which are specifically expressed in PPR lesions, may serve as an antioxidant in the affected coral tissue. Overall, this study provides new knowledge to our understanding of the role of CPs in coral immunity.